Social Prescribing and Lifestyle Medicine—A Remedy to Chronic Health Problems? - Baska, Alicja; Kurpas, Donata; Kenkre, Joyce; Vidal-Alaball, Josep; Petrazzuoli, Ferdinando; Dolan, Miriam; Śliż, Daniel; Robins, Joanne (International journal of environmental research and public health, 2021)
Social prescribing has been identified as a chance to take a holistic approach to people’s health and wellbeing, especially for people with one or more long-term conditions. Its systemic implementation was a part of the recent United Kingdom National Health Service Long Term Plan. With a lifestyle medicine focus on equipping patients in tools necessary for self-care and self-management of their lifestyle-related health problems that coexists with the need for creating an environment supporting healthy choices, a social prescribing model seems to offer a promising strategy for advancing lifestyle medicine. This idea was discussed during a meeting hosted by the Polish Society of Lifestyle Medicine in collaboration with European Rural and Isolated Practitioners Association, Polish Society of Young Family Doctors (“Młodzi Lekarze Rodzinni”), British Society of Lifestyle Medicine and European Lifestyle Medicine Council in June 2020. The aftermath—this position statement is an Authors’ attempt at summarizing the common ground for social prescribing and lifestyle medicine. It collects experiences of practitioners and researchers from five European countries as well as making recommendations for applying this model in Poland. Despite referring to local conditions, it might provide universal takeaway messages for any healthcare providers interested in combining social prescribing with lifestyle medicine practice.